Manajemen Mutu Pengelolaan Pendidikan Berbasis Madrasah Digital pada Madrasah Tsanawiyah di Kota Parepare: Digital Madrasa-Based Education Quality Management at Middle Islamic Schools in Parepare City - Muhammad Alwi; Abdul Halik; Andi Putri Ayu Darapati; Muh Mahsyar (Al-Musannif, 2024)
In the era of digital transformation, Islamic educational institutions, particularly madrasahs, face significant challenges in maintaining education quality while integrating digital technologies. A key issue lies in the gap between the current state of digital readiness and the expected standards of digital education management. This study aims to develop a model of quality management for digital-based education in Madrasah Tsanawiyah (MTs) in Parepare City, Indonesia. Using a qualitative approach with grounded theory methodology, data were collected through interviews, observations, and document analysis from selected MTs actively implementing digital programs. The findings reveal that although madrasahs have initiated various digital innovations—such as Android-based exams, online learning platforms, website utilization, and digital communication tools—implementation remains uneven due to limited infrastructure and technical capabilities. Despite these challenges, there is a strong institutional commitment to adapt. The proposed management model offers a strategic framework for integrating technology into educational processes and institutional management. The study has practical implications for improving policy, resource planning, and teacher training in the digitalization of Islamic education. It also provides a theoretical contribution to the field of education quality management in the context of digital madrasah transformation.